Efficiency of lung cancer screening in early diagnosis and treatment program among community residents in Nanshan district, Shenzhen city: a cross-sectional and 2-year follow-up survey - Yarui YANG; Xujun GUO; Yuzheng FAN; Han WANG; Shengbin LI; Juan HE; Chang MA; Junbo BAI; Shengyuan LIU (Zhongguo gonggong weisheng)
ObjectiveTo evaluate the effectiveness of a lung cancer screening program for early diagnosis and treatment of the disease among community residents in Nanshan district, Shenzhen city, Guangdong province, and to provide evidence for optimizing regional lung cancer prevention and control policies. MethodsA total of 11 000 residents aged 40 – 74 years were recruited from 59 communities in Nanshan district, Shenzhen city, Guangdong province, through publicity and mobilization from December 2020 to January 2022. A face-to-face questionnaire interview was conducted to collect relevant information to assess the lung cancer risk of the participants based on the China National Cancer Center Lung Cancer Model (NCC-LCm2021 Model). Participants identified as being at high risk for lung cancer underwent low-dose spiral computed tomography (LDCT) of the lungs. Participants at high risk for lung cancer who did not undergo LDCT were followed up. Participants with LDCT results of suspected lung cancer/positive lung nodules/semi-positive lung nodules were followed for 2 years. The effectiveness of lung cancer screening among participants was evaluated by analyzing the detection rate of participants at high risk for lung cancer, the screening rate of LDCT, the follow-up results of patients with lung nodules, and the cost-effectiveness of the program. ResultsOf the 8 266 (75.1% of all participants) who completed the risk assessment, 3 051 (36.9%) were identified as being at high risk for lung cancer based on the NCC-LCm2021 model, and the detection rates increased with increasing age for male, female, and total participants (χ2trend = 1 822.37, 2 209.14, and 4 020.10, all Ptrend < 0.001). Of the 3 051 participants at high risk for lung cancer, 1 952 (64.0%) underwent LDCT screening, with the highest screening rate (73.9%) among female participants aged 56 – 60 years. The LDCT screening detected 19 cases of suspected lung cancer (1.0%), 328 cases of positive lung nodules (16.9%), and 604 cases of semi-positive lung nodules (30.9%). The highest detection rate of suspected lung cancer was found in participants aged 71 – 74 years (1.6%); the highest detection rate of positive lung nodules was found in participants aged 66 – 70 years (19.4%); and the highest detection rate of semi-positive lung nodules was found in participants aged 51 – 55 years (36.9%). By the end of the 2-year health education follow-up, a total of 16 lung cancer cases were diagnosed among participants with suspected lung cancer/positive lung nodules/semi-positive lung nodules. The overall lung cancer detection rate was 193.6/100 000, and the lung cancer early detection rate was 87.5% for the screening program. For the screening program, the total cost was 1.304 million Chinese yuan (CNY); the per capita cost was 157.8 CNY; the cost-effectiveness ratio (CER) for each confirmed lung cancer case was 82 000 CNY; the average cost for each early-diagnosed lung cancer case was 93 000 CNY; and the early detection cost index (EDCI) was 0.22. The above indicators suggest a high cost-effectiveness of the program. ConclusionsThe lung cancer screening program for early diagnosis and treatment of the disease among community residents in Nanshan district, Shenzhen city, has achieved good results and the results suggest that more residents aged ≥ 50 years should be encouraged to participate the program to improve the effectiveness of the lung cancer early diagnosis and treatment program.